Heteroatomic ga-itq-13 molecular sieve and method for preparing the same

CN118954529BActive Publication Date: 2026-10-09CHINA UNIV OF PETROLEUM (BEIJING)
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310542985.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-15
Publication Date
2026-10-09
Estimated Expiration
2043-05-15

AI Technical Summary

Technical Problem

然而,现有技术中(CN105271295A、CN103979574A、CN102502683A、Microporous&MesoporousMaterials.2017,246,186-192等),ITQ-13分子筛晶粒的粒径较大,往往高达十几或几十微米,鲜少涉及小晶粒ITQ-13分子筛的制备方法

Benefits of technology

[0023] (1) The molecular sieve provided by the present invention contains heteroatoms, which can endow ITQ-13 molecular sieve with unique catalytic properties, thereby enabling it to become a unique functional catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118954529B_ABST
    Figure CN118954529B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of zeolite molecular sieve preparation, and discloses a heteroatom Ga-ITQ-13 molecular sieve and a preparation method thereof. The molecular sieve has an ITH structure, contains silicon, gallium, germanium, oxygen and optional aluminum in framework elements, the particle size of the molecular sieve crystal grains is 300-2000 nm, the total specific surface area is > 330 m 2 / g, and the total pore volume is > 0.300 cm 3 / g. The molecular sieve provided by the application contains heteroatoms, can endow the ITQ-13 molecular sieve with unique catalytic performance, and can make the ITQ-13 molecular sieve become a unique functional catalyst. The preparation method provided by the application has the advantages of short period, low cost, environmental friendliness, green efficiency and the like, and the particle size of the molecular sieve crystal grains is significantly reduced, and the texture properties such as the specific surface area and the pore volume are obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of zeolite molecular sieve preparation technology, specifically to a heteroatom Ga-ITQ-13 molecular sieve and its preparation method. Background Technology

[0002] ITQ-13 molecular sieve is a novel microporous material invented by A. Corma et al. (CN1512965A). It is the only three-dimensional orthogonal interconnected pore structure that combines nine-membered and ten-membered rings. Its framework type code is ITH. It is composed of silicon-oxygen tetrahedra and M-oxygen tetrahedra connected by oxygen bridges. M can be atoms such as gallium, aluminum, and germanium.

[0003] The unique pore structure of ITQ-13 molecular sieve effectively inhibits hydrogen transfer and aromatization reactions. It exhibits excellent shape selectivity in catalytic cracking, catalytic pyrolysis, and methanol-to-olefins reactions, significantly improving the selectivity of low-carbon olefin products, especially propylene. It holds promise for replacing traditional molecular sieves in low-carbon olefin production processes. Furthermore, ITQ-13 molecular sieve demonstrates strong catalytic potential in isomerization, propane dehydrogenation, and toluene disproportionation, possessing significant commercial value and promising industrial application prospects.

[0004] In recent years, reports on the synthesis of ITQ-13 zeolites (US20030171634A1, CN1512965A, CN103224242A, CN106698456A, CN102502683A, CN103979574A, CN105271295A, J. Catal. 2006, 238, 79-87, Angew. Chem. Int. Ed. 2020, 59, 15649-15655, etc.) have disclosed synthetic processes that, while improved upon traditional methods, still require the use of organic template agents to guide the formation of the target zeolite. These template agents are expensive, have complex preparation processes, and require high-temperature calcination during the subsequent demolding process. Furthermore, heteroatom sources hydrolyze in the alkaline medium of the template agent system to form insoluble hydroxide precipitates, which are difficult to integrate into the zeolite framework. Therefore, green synthesis routes without organic template agents have emerged in recent years in response to the trend of "green chemical engineering".

[0005] When ITQ-13 molecular sieve was first introduced, it was a pure silicon molecular sieve. Later, the intercalation of aluminum into the framework brought about corresponding acidity and catalytic activity. The introduction of specific metal or non-metal heteroatoms can maintain the original framework structure while modulating the physicochemical properties, stability, activity, and selectivity of the molecular sieve, thereby endowing the original molecular sieve with some unique catalytic reaction performance. The properties of the active component itself are also conducive to realizing its multifunctional catalysis.

[0006] On the other hand, small-crystal molecular sieves have a higher external specific surface area, shorter pores, and lower intracrystalline diffusion resistance, which helps reduce the accumulation of reactant and product molecules in the pores and the formation of carbon deposits, thereby improving the catalytic activity and lifetime of the molecular sieve. However, in existing technologies (CN105271295A, CN103979574A, CN102502683A, Microporous & Mesoporous Materials. 2017, 246, 186-192, etc.), the particle size of ITQ-13 molecular sieve crystals is relatively large, often reaching tens of micrometers, and there are very few methods for preparing small-crystal ITQ-13 molecular sieves.

[0007] In view of this, breakthroughs are urgently needed in the development of small-crystal ITQ-13 molecular sieves containing heteroatoms in template-free systems and their preparation methods. Summary of the Invention

[0008] One of the objectives of this invention is to provide a small-grained Ga-ITQ-13 molecular sieve containing framework heteroatoms.

[0009] A second objective of this invention is to provide a method for preparing the above-mentioned molecular sieves in a template-free system.

[0010] To achieve the above objectives, a first aspect of the present invention provides a heteroatom Ga-ITQ-13 molecular sieve having an ITH structure, wherein the framework elements include silicon, gallium, germanium, oxygen, and optionally aluminum, and the molar ratio of gallium to silicon, calculated as oxides, is 0.001-0.005.

[0011] The molecular sieve crystals have a particle size of 300-2000 nm and a total specific surface area >330 m². 2 / g, total pore volume > 0.300cm³ 3 / g.

[0012] A second aspect of the present invention provides a method for preparing heteroatom Ga-ITQ-13 molecular sieves, the method comprising:

[0013] (1) The crystallization guiding liquid, component a, component b and water I are mixed for the first time to obtain mixture A; component a contains silicon source I, germanium source I and optional aluminum source I; component b contains gallium source and fluorine source I;

[0014] The conditions for the first mixing include: being carried out under stirring conditions, with a stirring speed of 300-400 rpm, a temperature of 40-80℃, and a time of 16-24 h;

[0015] (2) The mixture A is placed in a reaction vessel for crystallization to obtain a crystallized product;

[0016] (3) The crystallized product is subjected to solid-liquid separation, and the obtained solid phase is washed and dried;

[0017] The nascent crystal guiding liquid is prepared by a method comprising the following steps:

[0018] Silicon source II, aluminum source II, germanium source II, fluorine source II and water II are mixed for the second time to obtain mixture B, and mixture B is precrystallized;

[0019] The conditions for the second mixing include: being carried out under stirring conditions, with a stirring speed of 300-360 rpm, a temperature of 50-70℃, and a time of 10-18 h;

[0020] The pre-crystallization conditions include a temperature of 80-135℃ and a time of 12-48h.

[0021] A third aspect of the present invention provides a heteroatom Ga-ITQ-13 molecular sieve prepared by the method described in the second aspect above.

[0022] This invention has at least the following advantages over the prior art:

[0023] (1) The molecular sieve provided by the present invention contains heteroatoms, which can endow ITQ-13 molecular sieve with unique catalytic properties, thereby enabling it to become a unique functional catalyst.

[0024] (2) The present invention uses a crystallization guiding liquid to replace the organic template agent in the traditional method, and synthesizes Ga-ITQ-13 molecular sieve with small crystal size and heteroatom through hydrothermal crystallization. This can effectively solve a series of problems such as high cost and environmental unfriendliness caused by the large-scale use of organic template agents in the traditional process.

[0025] (3) The template-free system used in this invention is under non-alkaline conditions. There are no excess sodium ions in the system, which is conducive to the effective introduction of framework heteroatoms. At the same time, it can also avoid the ammonium ion exchange step to form a hydrogen molecular sieve process with catalytic activity.

[0026] (4) The method for preparing heteroatom Ga-ITQ-13 molecular sieve provided by the present invention has the advantages of short cycle, low cost, environmental friendliness, green and efficient, and the particle size of molecular sieve crystals is significantly reduced, and the texture properties such as specific surface area and pore volume are significantly improved. Attached Figure Description

[0027] Figure 1 These are the XRD patterns of the molecular sieves prepared in Examples 1-6 and Comparative Examples 1-5 provided by the present invention;

[0028] Figure 2The XRD patterns of the characteristic diffraction peaks of the ITQ-13 molecular sieves prepared in Examples 1-6 and Comparative Example 3 provided by this invention are magnified at 2θ = 20°-25°.

[0029] Figure 3 This is a SEM image of the molecular sieve prepared in Comparative Example 1 provided by the present invention;

[0030] Figure 4 This is a SEM image of the molecular sieve prepared in Comparative Example 2 provided by the present invention;

[0031] Figure 5 This is a SEM image of the molecular sieve prepared in Comparative Example 3 provided by the present invention.

[0032] Figure 6 These are SEM-EDS images of the molecular sieve prepared in Example 1 of this invention, where Image A is an SEM image and Image B is a mapping image of Ga elements.

[0033] Figure 7 These are SEM-EDS images of the molecular sieve prepared in Example 2 of this invention, where Image A is an SEM image and Image B is a mapping image of Ga elements.

[0034] Figure 8 These are SEM-EDS images of the molecular sieve prepared in Example 3 of this invention, where Image A is the SEM image and Image B is the Ga element mapping image.

[0035] Figure 9 These are SEM-EDS images of the molecular sieve prepared in Example 4 of this invention, where Image A is an SEM image and Image B is a mapping image of Ga elements.

[0036] Figure 10 These are SEM-EDS images of the molecular sieve prepared in Example 5 of this invention, where Image A is an SEM image and Image B is a mapping image of Ga elements.

[0037] Figure 11 These are SEM-EDS images of the molecular sieve prepared in Example 6 of this invention, where Image A is an SEM image and Image B is a mapping image of Ga elements.

[0038] Figure 12 These are the FT-IR spectra of the molecular sieves prepared in Examples 1-6 and Comparative Example 3 provided by the present invention. Detailed Implementation

[0039] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0040] As previously stated, a first aspect of the present invention provides a heteroatom Ga-ITQ-13 molecular sieve having an ITH structure, wherein the framework elements include silicon, gallium, germanium, oxygen and optionally aluminum, and the molar ratio of gallium to silicon, calculated as oxides, is 0.001-0.005.

[0041] The molecular sieve crystals have a particle size of 300-2000 nm and a total specific surface area >330 m². 2 / g, total pore volume > 0.300cm³ 3 / g.

[0042] Preferably, the particle size of the molecular sieve crystals is 500-1500 nm.

[0043] As previously described, a second aspect of the present invention provides a method for preparing heteroatom Ga-ITQ-13 molecular sieves, the method comprising:

[0044] (1) The crystallization guiding liquid, component a, component b and water I are mixed for the first time to obtain mixture A; component a contains silicon source I, germanium source I and optional aluminum source I; component b contains gallium source and fluorine source I;

[0045] The conditions for the first mixing include: being carried out under stirring conditions, with a stirring speed of 300-400 rpm, a temperature of 40-80℃, and a time of 16-24 h;

[0046] (2) The mixture A is placed in a reaction vessel for crystallization to obtain a crystallized product;

[0047] (3) The crystallized product is subjected to solid-liquid separation, and the obtained solid phase is washed and dried;

[0048] The nascent crystal guiding liquid is prepared by a method comprising the following steps:

[0049] Silicon source II, aluminum source II, germanium source II, fluorine source II and water II are mixed for the second time to obtain mixture B, and mixture B is precrystallized;

[0050] The conditions for the second mixing include: being carried out under stirring conditions, with a stirring speed of 300-360 rpm, a temperature of 50-70℃, and a time of 10-18 h;

[0051] The pre-crystallization conditions include a temperature of 80-135℃ and a time of 12-48h.

[0052] According to a preferred embodiment, in step (1),

[0053] Mix the crystal guiding liquid, component a and water I to obtain mixture A1;

[0054] Mix the mixture A1 and component b together to obtain mixture A;

[0055] The conditions for mixing I and mixing II each independently include: being carried out under stirring conditions, with a stirring speed of 300-400 rpm, a temperature of 40-80℃, and a time of 10-24 h.

[0056] Preferably, the amounts of silicon source I, aluminum source I, germanium source I, gallium source I, and fluorine source I are such that the molar amounts of each component in the mixture A satisfy the following: SiO2 / Al2O3 ≥ 20, GeO2 / SiO2 = 0.01-1.0, Ga2O3 / SiO2 = 0.001-0.015, F / SiO2 = 0.01-2.0, and H2O / SiO2 = 50-150. More preferably, the amounts of silicon source I, aluminum source I, germanium source I, gallium source I, and fluorine source I are such that the molar amounts of each component in the mixture A satisfy the following: SiO2 / Al2O3 ≥ 40, GeO2 / SiO2 = 0.04-0.08, Ga2O3 / SiO2 = 0.0048-0.0080, F / SiO2 = 0.8-1.5, and H2O / SiO2 = 100-130.

[0057] Preferably, the amounts of silicon source II, aluminum source II, germanium source II, and fluorine source II are such that the molar content of each component in the precursor crystal guiding liquid satisfies the following: SiO2 / Al2O3 ≥ 20, GeO2 / SiO2 = 0.01-1.0, F / SiO2 = 0.01-2.0, H2O / SiO2 = 10-70. More preferably, the amounts of silicon source II, aluminum source II, germanium source II, and fluorine source II are such that the molar content of each component in the precursor crystal guiding liquid satisfies the following: SiO2 / Al2O3 ≥ 40, GeO2 / SiO2 = 0.04-0.08, F / SiO2 = 0.8-1.5, H2O / SiO2 = 30-50.

[0058] Preferably, the weight ratio of the crystallization guiding liquid to the silicon source I (based on SiO2) is 5-50:100. More preferably, the weight ratio of the crystallization guiding liquid to the silicon source I (based on SiO2) is 15-30:100. The inventors of this invention have found that the molecular sieve obtained under this preferred condition has a higher bulk gallium content and better physicochemical properties (smaller particle size, better texture properties).

[0059] Preferably, silicon source I and silicon source II are each independently selected from at least one of water glass, silica sol, coarse-porous silicon, silica, and tetraethyl orthosilicate.

[0060] In a preferred embodiment, aluminum source I and aluminum source II are each independently selected from at least one of boehmite, sodium aluminate, aluminum isopropoxide, aluminum sulfate, aluminum oxide, and aluminum hydroxide.

[0061] Preferably, the fluorine source I and the fluorine source II are each independently selected from at least one of hydrofluoric acid, ammonium fluoride, ammonium hydrogen fluoride, and potassium fluoride.

[0062] Preferably, the gallium source is selected from at least one of gallium chloride, gallium nitrate, and gallium oxide.

[0063] It should be noted that the present invention does not impose any particular restrictions on the types of germanium source I and germanium source II. Those skilled in the art can select them based on known technical means in the art. The following text of the present invention provides a preferred specific embodiment, which should not be construed as a limitation of the present invention.

[0064] According to another preferred embodiment, the crystallization is dynamic crystallization, and the conditions for dynamic crystallization include: crystallization for 24-120 hours at a rotational speed of 20-30 rpm, a temperature of 130-200°C, and an autogenous pressure.

[0065] It should be noted that the present invention does not impose any particular limitations on the methods of solid-liquid separation and washing. Those skilled in the art can make selections by combining known technical means in the art. The following text of the present invention provides a preferred specific embodiment, which should not be construed as a limitation of the present invention.

[0066] Preferably, the drying conditions include a temperature of 100-120°C and a time of 10-24 hours.

[0067] As previously stated, a third aspect of the present invention provides a heteroatom Ga-ITQ-13 molecular sieve prepared by the method described in the second aspect above.

[0068] The present invention will be described in detail below through examples.

[0069] In the following examples, unless otherwise specified, all raw materials used were commercially purchased.

[0070] raw material:

[0071] Silicon source:

[0072] Water glass: SiO2 content 27.70wt%, Na2O content 8.96wt%, purchased from Beijing Hongxing Guangsha Chemical Building Materials Co., Ltd.;

[0073] Silica sol: SiO2 content 30wt%, purchased from Tianjin Guangfu Fine Chemical Research Institute;

[0074] Tetraethyl orthosilicate: analytical grade, SiO2 content 28.84 wt%, purchased from Shanghai Maclean Biochemical Technology Co., Ltd.

[0075] Silica: Purchased from Shanghai Maclean Biochemical Technology Co., Ltd.;

[0076] Aluminum source:

[0077] Aluminum isopropoxide: analytical grade, content ≥98% wt%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0078] Boehmite: Al2O3 content 72.5wt%, purchased from Shandong Branch of Aluminum Corporation of China Limited;

[0079] Sodium aluminate: chemically pure, Al2O3 content ≥45.0wt%, purchased from Tianjin Guangfu Fine Chemical Research Institute;

[0080] Aluminum sulfate: analytical grade, content ≥99wt%, purchased from Tianjin Guangfu Technology Development Co., Ltd.

[0081] Fluorine source:

[0082] Ammonium fluoride: analytical grade, content ≥98.0 wt%, purchased from Shanghai Maclean Biochemical Technology Co., Ltd.;

[0083] Germanium source:

[0084] Germanium oxide: analytical grade, content ≥99.9 wt%, purchased from Tianjin Guangfu Fine Chemical Research Institute;

[0085] Gallium source:

[0086] Gallium nitrate: analytical grade, purity ≥99.9 wt%, purchased from Shanghai Maclean Biochemical Technology Co., Ltd.

[0087] Gallium chloride: analytical grade, content ≥99wt%, purchased from Tianjin Guangfu Technology Development Co., Ltd.

[0088] Preparation Example 1: Preparation of Pre-crystal Guiding Fluid

[0089] 46.50g of tetraethyl orthosilicate, 1.88g of aluminum isopropoxide, 1.17g of germanium oxide, 10.57g of ammonium fluoride and 184.81g of deionized water were mixed for the second time to obtain mixture B. Mixture B was then pre-crystallized to obtain crystallization guide liquid Y1, which was then sealed and stored.

[0090] The second mixing conditions are: carried out under stirring conditions, with a stirring speed of 340 rpm, a temperature of 60℃, and a time of 15 h;

[0091] The pre-crystallization conditions were: temperature 115℃, time 36h;

[0092] In the crystallization guiding liquid Y1, the molar amounts of SiO2 / Al2O3 are 50, GeO2 / SiO2 are 0.05, F / SiO2 are 1.28, and H2O / SiO2 are 46.

[0093] Comparative preparation example 1:

[0094] 46.50g of tetraethyl orthosilicate, 1.88g of aluminum isopropoxide, 1.17g of germanium oxide, 10.57g of ammonium fluoride and 184.81g of deionized water were mixed for the second time, and then subjected to low-temperature pre-crystallization to obtain the crystallization guide liquid DY1, which was then sealed and stored.

[0095] The conditions for the second mixing are: the mixture is carried out under stirring conditions, with a stirring speed of 325 rpm, a temperature of 80°C, and a time of 22 h;

[0096] The pre-crystallization conditions were: temperature 140℃, time 36h;

[0097] In the crystallization guiding liquid DY1, the molar amounts of SiO2 / Al2O3 are 50, GeO2 / SiO2 = 0.05, F / SiO2 = 1.28, and H2O / SiO2 = 46.

[0098] Example 1

[0099] (1) Mix 10.17g of crystal guiding liquid Y1, 23.50g of tetraethyl orthosilicate, 0.96g of aluminum isopropoxide, 0.47g of germanium oxide and 203.04g of deionized water to obtain a mixture A1 that does not contain autogenous ethanol and isopropanol.

[0100] The conditions for mixing I are: it is carried out under stirring conditions, with a stirring speed of 360 rpm, a temperature of 60℃, and a time of 12 h;

[0101] The weight ratio of the crystal guiding liquid to silicon source I (calculated as SiO2) is 15:100.

[0102] Mixture A1, 0.46 g gallium nitrate, and 3.34 g ammonium fluoride are mixed in step II to obtain mixture A;

[0103] The conditions for mixing II were: mixing was carried out under stirring conditions, with a stirring speed of 320 rpm, a temperature of 60°C, and a time of 8 hours;

[0104] The molar amounts of each component in mixture A satisfy the following conditions: SiO2 / Al2O3 = 50, GeO2 / SiO2 = 0.04, Ga2O3 / SiO2 = 0.0080, F / SiO2 = 0.8, H2O / SiO2 = 100;

[0105] (2) Mixture A was placed in a stainless steel reactor with a polytetrafluoroethylene liner for dynamic crystallization to obtain the crystallized product.

[0106] The conditions for dynamic crystallization were: crystallization at a rotation speed of 26 rpm, a temperature of 170 °C, and autogenous pressure for 72 h.

[0107] (3) The crystallized product was filtered, and the obtained solid phase was washed and dried to obtain Ga-ITQ-13 molecular sieve S1;

[0108] The drying conditions are: temperature 100℃, time 12h.

[0109] Example 2

[0110] (1) Mix 16.27g of nascent crystal guiding liquid Y1, 24.47g of water glass, 1.04g of aluminum isopropoxide, 0.59g of germanium oxide and 233.50g of deionized water to obtain a mixture A1 that does not contain self-generated isopropanol;

[0111] The conditions for mixing I are: it is carried out under stirring conditions, with a stirring speed of 345 rpm, a temperature of 55℃, and a time of 14 h;

[0112] The weight ratio of the crystal guiding liquid to silicon source I (calculated as SiO2) is 24:100.

[0113] Mixture A1, 0.34 g gallium nitrate, and 5.34 g ammonium fluoride are mixed in step II to obtain mixture A;

[0114] The conditions for mixing II were: mixing was carried out under stirring conditions, with a stirring speed of 330 rpm, a temperature of 55°C, and a time of 6.5 h;

[0115] The molar amounts of each component in mixture A satisfy the following: SiO2 / Al2O3 = 45, GeO2 / SiO2 = 0.05, Ga2O3 / SiO2 = 0.0059, F / SiO2 = 1.28, H2O / SiO2 = 115;

[0116] (2) Mixture A was placed in a stainless steel reactor with a polytetrafluoroethylene liner for dynamic crystallization to obtain the crystallized product.

[0117] The conditions for dynamic crystallization were: crystallization at a rotation speed of 25 rpm, a temperature of 180 °C, and autogenous pressure for 48 h.

[0118] (3) The crystallized product was filtered, and the obtained solid phase was washed and dried to obtain Ga-ITQ-13 molecular sieve S2;

[0119] The drying conditions are: temperature 100℃, time 12h.

[0120] Example 3

[0121] (1) Mix 20.33g of primordial crystal guiding liquid Y1, 22.59g of silica sol, 0.38g of sodium aluminate, 0.94g of germanium oxide and 263.95g of deionized water to obtain mixture A1;

[0122] The conditions for mixing I are: it is carried out under stirring conditions, with a stirring speed of 350 rpm, a temperature of 65℃, and a time of 15 h;

[0123] The weight ratio of the crystal guiding liquid to silicon source I (calculated as SiO2) is 30:100.

[0124] Mixture A1, 0.19 g gallium chloride, and 6.26 g ammonium fluoride were mixed in II to obtain mixture A;

[0125] The conditions for mixing II were: mixing was carried out under stirring conditions, with a stirring speed of 330 rpm, a temperature of 65°C, and a time of 7 h;

[0126] The molar amounts of each component in mixture A satisfy the following: SiO2 / Al2O3 = 50, GeO2 / SiO2 = 0.08, Ga2O3 / SiO2 = 0.0048, F / SiO2 = 1.5, H2O / SiO2 = 130;

[0127] (2) Mixture A was placed in a stainless steel reactor with a polytetrafluoroethylene liner for dynamic crystallization to obtain the crystallized product.

[0128] The conditions for dynamic crystallization were: crystallization at a rotation speed of 26 rpm, a temperature of 175 °C, and autogenous pressure for 60 h.

[0129] (3) The crystallized product was filtered, and the obtained solid phase was washed and dried to obtain Ga-ITQ-13 molecular sieve S3;

[0130] The drying conditions are: temperature 100℃, time 12h.

[0131] Example 4

[0132] (1) Mix 13.62g of primordial crystal guiding liquid Y1, 6.78g of silica, 0.39g of pseudoboehmite, 1.88g of germanium oxide and 274.11g of deionized water to obtain mixture A1;

[0133] The conditions for mixing I were: mixing was carried out under stirring conditions, with a stirring speed of 380 rpm, a temperature of 50°C, and a time of 11 h.

[0134] The weight ratio of the crystal guiding liquid to silicon source I (calculated as SiO2) is 20:100.

[0135] Mixture A1, 0.21 g gallium nitrate, and 2.92 g ammonium fluoride were mixed in step II to obtain mixture A;

[0136] The conditions for mixing II were: mixing was carried out under stirring conditions, with a stirring speed of 355 rpm, a temperature of 50°C, and a time of 6 hours;

[0137] The molar amounts of each component in mixture A satisfy the following: SiO2 / Al2O3 = 40, GeO2 / SiO2 = 0.16, Ga2O3 / SiO2 = 0.0036, F / SiO2 = 0.7, H2O / SiO2 = 135;

[0138] (2) Mixture A was placed in a stainless steel reactor with a polytetrafluoroethylene liner for dynamic crystallization to obtain the crystallized product.

[0139] The conditions for dynamic crystallization were: crystallization at a rotation speed of 25 rpm, a temperature of 145 °C, and an autogenous pressure for 120 h.

[0140] (3) The crystallized product was filtered, and the obtained solid phase was washed and dried to obtain Ga-ITQ-13 molecular sieve S4.

[0141] The drying conditions are: temperature 100℃, time 12h.

[0142] Example 5

[0143] (1) Mix 5.98g of crystal guiding liquid Y1, 23.53g of tetraethyl orthosilicate, 1.55g of aluminum sulfate, 0.71g of germanium oxide and 197.27g of deionized water to obtain a mixture A1 that does not contain autogenous ethanol;

[0144] The conditions for mixing I are: it is carried out under stirring conditions, with a stirring speed of 360 rpm, a temperature of 60℃, and a time of 12 h;

[0145] The weight ratio of the crystal guiding liquid to silicon source I (calculated as SiO2) is 8:100.

[0146] Mixture A1, 0.10 g gallium chloride, and 3.34 g ammonium fluoride are mixed in II to obtain mixture A;

[0147] The conditions for mixing II were: mixing was carried out under stirring conditions, with a stirring speed of 345 rpm, a temperature of 60°C, and a time of 7 h;

[0148] The molar amounts of each component in mixture A satisfy the following: SiO2 / Al2O3 = 50, GeO2 / SiO2 = 0.06, Ga2O3 / SiO2 = 0.0025, F / SiO2 = 0.8, H2O / SiO2 = 97;

[0149] (2) Mixture A was placed in a stainless steel reactor with a polytetrafluoroethylene liner for dynamic crystallization to obtain the crystallized product.

[0150] The conditions for dynamic crystallization were: crystallization at a rotation speed of 22 rpm, a temperature of 175℃, and autogenous pressure for 60 h.

[0151] (3) The crystallized product was filtered, and the obtained solid phase was washed and dried to obtain Ga-ITQ-13 molecular sieve S5;

[0152] The drying conditions are: temperature 100℃, time 12h.

[0153] Example 6

[0154] (1) Mix 25.46g of crystal guiding liquid Y1, 26.55g of tetraethyl orthosilicate, 0.26g of germanium oxide and 306.27g of deionized water to obtain a mixture A1 that does not contain self-generated ethanol;

[0155] The conditions for mixing I are: it is carried out under stirring conditions, with a stirring speed of 360 rpm, a temperature of 60℃, and a time of 14 h;

[0156] Mixture A1, 0.13 g gallium nitrate, and 5.42 g ammonium fluoride were mixed in II to obtain mixture A;

[0157] The conditions for mixing II were: mixing was carried out under stirring conditions, with a stirring speed of 345 rpm, a temperature of 60°C, and a time of 6 hours;

[0158] The molar amounts of each component in mixture A satisfy the following: GeO2 / SiO2 = 0.02, Ga2O3 / SiO2 = 0.0019, F / SiO2 = 1.15, H2O / SiO2 = 134;

[0159] (2) Mixture A was placed in a stainless steel reactor with a polytetrafluoroethylene liner for dynamic crystallization to obtain the crystallized product.

[0160] The conditions for dynamic crystallization were: crystallization at a rotation speed of 30 rpm, a temperature of 185 °C, and autogenous pressure for 24 h.

[0161] (3) The crystallized product was filtered, and the obtained solid phase was washed and dried to obtain Ga-ITQ-13 molecular sieve S6.

[0162] The drying conditions are: temperature 100℃, time 12h.

[0163] Comparative Example 1

[0164] 251.24 g of 0.22 mol / L dihydroxyhexane diammonium aqueous solution, 23.50 g of tetraethyl orthosilicate, and 0.59 g of germanium oxide were stirred at 360 rpm for 14 h in a constant temperature water bath at 60 °C to obtain mixture I, which does not contain autogenous ethanol.

[0165] Mixture I, 0.96 g aluminum isopropoxide, 1.02 g ITQ-13 seed crystals and 5.34 g ammonium fluoride were stirred at 345 rpm for 6 h in a constant temperature water bath at 60 °C to obtain mixture II;

[0166] Mixture II was placed in a stainless steel reactor with a polytetrafluoroethylene liner and crystallized for 72 hours at a rotation speed of 26 rpm, a temperature of 170 °C, and autogenous pressure to obtain the crystallized product.

[0167] The crystallized product was filtered, and the resulting solid phase was washed and dried to obtain ITQ-13 molecular sieve DS1.

[0168] The drying conditions are: temperature 100℃, time 12h.

[0169] Comparative Example 2

[0170] This comparative example uses a similar method to Comparative Example 1, except that:

[0171] Mixture I, 0.96 g aluminum isopropoxide, 1.02 g ITQ-13 seed crystals, 0.46 g gallium nitrate and 5.34 g ammonium fluoride were stirred at 345 rpm for 6 h in a constant temperature water bath at 60 °C to obtain mixture II;

[0172] All other conditions were the same as those in Comparative Example 1, and Ga-ITQ-13 molecular sieve DS2 was prepared.

[0173] Comparative Example 3

[0174] This comparative example was conducted using a method similar to that of Example 1, except that:

[0175] In step (1), mixture A1 and 3.34 g of ammonium fluoride are mixed (II) to obtain mixture A; and

[0176] In step (2), the conditions for dynamic crystallization are: crystallization for 72 hours at a rotation speed of 25 rpm, a temperature of 160 °C, and an autogenous pressure.

[0177] All other conditions were the same as in Example 1, and ITQ-13 molecular sieve DS3 was obtained.

[0178] Comparative Example 4

[0179] This comparative example was conducted using a method similar to that of Example 1, except that:

[0180] The initial crystal guiding liquid Y1 was replaced with an equal weight of the initial crystal guiding liquid DY1, and all other conditions were the same as in Example 1, to obtain Ga-ITQ-13 molecular sieve DS4.

[0181] Comparative Example 5

[0182] This comparative example was conducted using a method similar to that of Example 1, except that:

[0183] In step (1), the temperature in both Mixing I and Mixing II was adjusted to 90°C, and the other conditions were the same as in Example 1, to obtain Ga-ITQ-13 molecular sieve DS5.

[0184] Test case

[0185] The molecular sieves prepared in the examples and comparative examples were subjected to the following performance tests. Some test results are shown in Tables 1 and 2, and others are shown in... Figures 1-12 :

[0186] (1) XRD data were obtained using an X-ray diffractometer (manufacturer: PANalytical, Netherlands; model: X'Pert Powder);

[0187] (2) SEM-EDS images were obtained using a field emission scanning electron microscope (manufacturer: ZEISS, Germany, model: GeminiSEM300);

[0188] (3) Elemental analysis data were obtained using an X-ray fluorescence spectrometer (manufacturer: PANalytical, Netherlands; model: Petro-AxiosMAX), as shown in Table 2.

[0189] (4) The specific surface area and pore volume data of the molecular sieve under test were obtained by N2 physical adsorption at -196℃ using a specific surface area and pore size distribution analyzer (manufacturer: Micromeritics, USA, model: TriStar3020). See Table 1 for details.

[0190] (5) Infrared skeleton vibration data were obtained using an infrared spectrometer (manufacturer: Thermo, model: Fisher Nicolet IS10).

[0191] Table 1

[0192]

[0193] Table 2

[0194] Example 1 90.830 1.115 1.275 6.149 Example 2 90.691 0.907 1.019 6.183 Example 3 90.938 0.827 0.879 6.413 Example 4 91.251 0.699 0.769 6.440 Example 5 90.898 0.713 0.511 6.458 Example 6 91.441 0 0.371 6.281 Comparative Example 1 91.285 1.393 0 5.749 Comparative Example 2 91.813 1.196 0.601 5.683 Comparative Example 3 91.948 0.617 0 6.416 Comparative Example 4 91.016 0.610 0.965 6.331 Comparative Example 5 90.947 0.559 1.107 6.428

[0195] By comparing the data of Comparative Example 1 and Comparative Example 2, it can be seen that the particle size of ITQ-13 molecular sieves decreases after adding gallium nitrate to the template agent system.

[0196] X-ray fluorescence spectroscopy measurements show that the Ga2O3 / SiO2 ratio in Ga-ITQ-13 molecular sieve DS2 is 0.0021, and the Ga2O3 / SiO2 ratio in Ga-ITQ-13 molecular sieve S1 is 0.0045. It can be seen that because the template agent system is in a strongly alkaline environment, gallium species are prone to forming insoluble precipitates when exposed to alkali, making it difficult for them to attach to the framework. Therefore, under the same gallium-silicon ratio, the gallium-silicon ratio (i.e., Ga2O3 / SiO2) in the molecular sieve obtained by the template agent method is significantly smaller than that in the molecular sieve obtained by the method provided in this invention.

[0197] By comparing the data of Comparative Example 1 and Comparative Example 3, it can be seen that the particle size of the ITQ-13 molecular sieve obtained by the method provided by the present invention is significantly smaller than that of the ITQ-13 molecular sieve obtained in the template agent system.

[0198] Figure 1 These are the XRD patterns of the molecular sieves prepared in Examples 1-6 and Comparative Examples 1-5 of this invention. As can be seen from the figures, the molecular sieves obtained after introducing different amounts of gallium are all pure-phase ITQ-13 molecular sieves, and the intensity of the crystal diffraction peaks gradually decreases with increasing gallium content.

[0199] Figure 2The images show the magnified XRD patterns of the characteristic diffraction peaks of the ITQ-13 molecular sieves prepared in Examples 1-6 and Comparative Example 3 of this invention at 2θ = 20°-25°. As can be seen from the figures, compared to before gallium introduction, the characteristic peaks of the molecular sieves are significantly shifted towards higher angles, fully demonstrating that gallium atoms have successfully entered the framework. When the amount of gallium introduced is similar, the Ga-ITQ-13 molecular sieve S6 prepared without the addition of aluminum source I in the reaction system shows a larger shift towards higher angles, while the Ga-ITQ-13 molecular sieve S5, due to the presence of framework aluminum, shows a slightly smaller shift towards higher angles than Ga-ITQ-13 molecular sieve S6.

[0200] Figures 3-5 These are SEM images of the molecular sieves prepared in Comparative Examples 1-3 provided by this invention. Figures 3-5 It can be seen that even without the introduction of heteroatoms, the particle size of the ITQ-13 molecular sieve obtained by the method provided in this invention is still smaller than that obtained by the template agent method, and the introduction of gallium species into the template agent system can also significantly reduce the particle size of the ITQ-13 molecular sieve.

[0201] Figures 6-11 These are SEM-EDS images of the molecular sieves prepared in Examples 1-6 of this invention. From... Figures 6-11 As can be seen, the gallium incorporation did not affect the morphology of the ITQ-13 molecular sieve. With the increase of gallium incorporation, the grain size decreased significantly, while the crystals gradually agglomerated into spherical shapes. In addition, the gallium species introduced through in-situ synthesis were uniformly distributed in the ITQ-13 molecular sieve; with the increase of gallium incorporation, the gallium content in the sample increased sequentially, as evidenced by the appearance of more and more gallium element dots in the mapping diagram.

[0202] Figure 12 These are the FT-IR spectra of the molecular sieves prepared in Examples 1-6 and Comparative Example 3 of this invention. As can be seen from the figures, the background framework vibrational absorption peaks of the gallium-introduced molecular sieves (Ga-ITQ-13 molecular sieves S1-S6) show a slight redshift compared to the gallium-free molecular sieve (ITQ-13 molecular sieve DS3), and the absorption peaks of molecular sieves S1-S5 at 1385 cm⁻¹ are also shown. -1 The appearance of a new characteristic absorption peak indicates that because the mass of gallium atoms is greater than that of silicon and aluminum atoms in the original framework, the Ga-O bond length increases, the reduced mass increases, and the bond force constant decreases, thus causing the absorption peak to shift towards lower wavenumbers. Furthermore, the incorporation of gallium into the ITQ-13 molecular sieve framework forms new Ga-O-Si bonds, or there is some interaction between gallium and the existing Si-O-Si or Al-O-Si bonds, causing slight changes in its framework structure and resulting in new absorption peaks.

[0203] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A method for preparing heteroatom Ga-ITQ-13 molecular sieves, characterized in that, The method includes: (1) The crystallization guiding liquid, component a, component b and water I are mixed for the first time to obtain mixture A; component a contains silicon source I, germanium source I and aluminum source I; component b contains gallium source and fluorine source I; The conditions for the first mixing include: being carried out under stirring conditions, with a stirring speed of 300-400 rpm, a temperature of 40-80℃, and a time of 16-24 h; (2) The mixture A is placed in a reaction vessel for crystallization to obtain a crystallized product; (3) The crystallized product is subjected to solid-liquid separation, and the resulting solid phase is washed and dried; The crystal guide fluid is prepared by the following steps: Silicon source II, aluminum source II, germanium source II, fluorine source II and water II are mixed for the second time to obtain mixture B, and mixture B is precrystallized; The conditions for the second mixing include: being carried out under stirring conditions, with a stirring speed of 300-360 rpm, a temperature of 50-70℃, and a time of 10-18 h; The pre-crystallization conditions include: a temperature of 80-135℃ and a time of 12-48h; The amounts of silicon source I, aluminum source I, germanium source I, gallium source, and fluorine source I are such that the molar amounts of each component in the mixture A satisfy the following: SiO2 / Al2O3≥20, GeO2 / SiO2=0.01-1.0, Ga2O3 / SiO2=0.001-0.015, F / SiO2=0.01-2.0, H2O / SiO2=50-150; The amounts of silicon source II, aluminum source II, germanium source II, and fluorine source II are such that the molar amounts of each component in the primordial crystal guiding liquid satisfy the following: SiO2 / Al2O3≥20, GeO2 / SiO2=0.01-1.0, F / SiO2=0.01-2.0, H2O / SiO2=10-70.

2. The method according to claim 1, wherein, The weight ratio of the primordial guiding liquid to the silicon source I (calculated as SiO2) is 5-50:

100.

3. The method according to claim 1 or 2, wherein, The silicon source I and the silicon source II are each independently selected from at least one of water glass, silica sol, coarse-porous silicon, silica, and tetraethyl orthosilicate.

4. The method according to claim 1 or 2, wherein, The aluminum source I and the aluminum source II are each independently selected from at least one of boehmite, sodium aluminate, aluminum isopropoxide, aluminum sulfate, aluminum oxide, and aluminum hydroxide.

5. The method according to claim 1 or 2, wherein, The fluorine source I and the fluorine source II are each independently selected from at least one of hydrofluoric acid, ammonium fluoride, ammonium hydrogen fluoride, and potassium fluoride.

6. The method according to claim 1 or 2, wherein, The gallium source is selected from at least one of gallium chloride, gallium nitrate, and gallium oxide.

7. The method according to claim 1 or 2, wherein, The crystallization is dynamic crystallization, and the conditions for dynamic crystallization include: crystallization for 24-120 hours at a rotation speed of 20-30 rpm, a temperature of 130-200℃, and autogenous pressure.

Citation Information

Patent Citations

  • Preparation method of ITQ-13 molecular sieve in non-concentrated-gel system

    CN102502683A

  • Low cost method for rapidly synthesizing ITQ-13 molecular sieve

    CN103224242A

  • Method for synthesizing molecular sieve by using solid phase

    CN103979574A

  • Method for preparing ITQ-13 molecular sieve by solvent-free synthesis

    CN105271295A

  • Method for synthesizing aluminum-containing ITQ-13 molecular sieve with one-step method by linearpoly quaternary ammonium base organic template

    CN106698456A